2023
DOI: 10.3390/su152316265
|View full text |Cite
|
Sign up to set email alerts
|

Company-Level Factors of Non-Financial Reporting Quality under a Mandatory Regime: A Systematic Review of Empirical Evidence in the European Union

Oana Marina Radu,
Voicu D. Dragomir,
Ningshan Hao

Abstract: The relationship between non-financial reporting quality (NFRQ) and various company-level factors has been studied extensively, considering the mandatory requirements applicable under the Non-Financial Reporting Directive 2014/95/EU (NFRD) of the European Union. The purpose of this research is to systematize the results of previous published studies on the relationship between NFRQ and company size, financial performance, corporate governance, market performance, and sustainability performance, under a mandato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Besides corporate aspects of company size and profitability, other research has found additional influencing factors, such as stock index rating, belonging to business sectors with a higher sustainability impact, and voluntary reporting experience, as seen in the studies of Mion & Loza (2019); Gerwing et al (2022); Radu et al (2023), Venturelli et al (2017) and Wang et al (2018).…”
Section: Reporting Factorsmentioning
confidence: 99%
“…Besides corporate aspects of company size and profitability, other research has found additional influencing factors, such as stock index rating, belonging to business sectors with a higher sustainability impact, and voluntary reporting experience, as seen in the studies of Mion & Loza (2019); Gerwing et al (2022); Radu et al (2023), Venturelli et al (2017) and Wang et al (2018).…”
Section: Reporting Factorsmentioning
confidence: 99%